Legal Protection For Wives Who Are Victims Of Domestic Violence Based On Law no. 23 of 2004 - Arie Prayogi; Lidya Rahmadhani Hasibuan; Fitria Ramadhani Siregar (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Violence against Wives committed by Husbands is often ignored and not seen as a serious problem. In addition, it is necessary to clarify the responsibility of the Husband as the perpetrator of domestic violence and find out how to resolve it legally. And the formulation of the problem in my thesis is How is the Law Enforcement Regarding Domestic Violence Based on Legislation, How is the Legal Protection for Wives Who Are Victims of Domestic Violence and How is the Legal Analysis of the Criminal Act of Committing Physical Violence in the Household Scope Committed by Husbands Against Wives in Decision Number 1329 / Pid.Sus / 2023 / Pn Mdn. The nature of the research in writing the thesis uses descriptive analysis, the type of research uses Normative law while the data collection method uses Library Research, and the type of data in this study uses Primary Data. Many settlements of domestic violence cases do not fulfill a sense of justice, especially for victims in the household. law enforcement in implementing protection for victims of domestic violence according to Law Number 23 of 2004 concerning the Elimination of Domestic Violence is very much needed, especially domestic violence.The results of this study conclude that the occurrence of domestic violence shows the imbalance of the position of husband and wife in living a household life. Legal protection for victims of domestic violence according to Law Number 23 of 2004 concerning the Elimination of Domestic Violence is very much needed because of all forms of violence, especially domestic violence.